Materials science and technology : a comprehensive treatment. Volume 11, Structure and properties of ceramics / edited by R.W. Cahn, P. Haasen, E.J. Kramer; Vol. editor : Michael V. Swain - Swain, Michael V.
Vol. 11 Structure and properties of ceramics in 1994